2015
DOI: 10.3109/10428194.2015.1014360
|View full text |Cite
|
Sign up to set email alerts
|

Clinically significant responses achieved with romidepsin across disease compartments in patients with cutaneous T-cell lymphoma

Abstract: Cutaneous T-cell lymphoma (CTCL) is a rare heterogeneous group of non-Hodgkin lymphomas that arises in the skin but can progress to systemic disease (lymph nodes, blood, viscera). Historically, in clinical trials of CTCL there has been little consistency in how responses were defined in each disease “compartment”; some studies only assessed responses in the skin. The histone deacetylase inhibitor romidepsin is approved by the US Food and Drug Administration for the treatment of CTCL in patients who have receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The greatest DOR was reported for acitretin (median DOR: 28.1 months) [77], with the highest PFS seen with brentuximab vedotin (median PFS 15.8, 57.6, and 116.4 months in three studies) [57,61,62]; median PFS with alemtuzumab was 56 months [33]. The median DOR was ≤28 months for other approved therapies [47,[68][69][70][71]73,76,77,[80][81][82], ≤17 months for conventional therapies [59,78] and <12 months for investigational therapies [61][62][63]75,83,84]. Median PFS was ≤13 months for other investigational, approved, and conventional therapies [25,63,64,75,85,86].…”
Section: Discussionmentioning
confidence: 99%
“…The greatest DOR was reported for acitretin (median DOR: 28.1 months) [77], with the highest PFS seen with brentuximab vedotin (median PFS 15.8, 57.6, and 116.4 months in three studies) [57,61,62]; median PFS with alemtuzumab was 56 months [33]. The median DOR was ≤28 months for other approved therapies [47,[68][69][70][71]73,76,77,[80][81][82], ≤17 months for conventional therapies [59,78] and <12 months for investigational therapies [61][62][63]75,83,84]. Median PFS was ≤13 months for other investigational, approved, and conventional therapies [25,63,64,75,85,86].…”
Section: Discussionmentioning
confidence: 99%
“…50 In the trial of Whittaker et al, 49 therapeutic responses were seen at all evaluated disease sites, with a 40% rate of response (38 of 96 patients) among patients with erythroderma or other skin disease, a 35% response rate among those with lymphadenopathy (13 of 37 patients), and a 32% rate of response in those with blood involvement (12 of 37 patients), including 10 of 13 patients with high blood tumor burden. 49,51 Also in this trial, a clinically meaningful reduction in pruritus (CMRP) was seen in 43% of patients (28 of 65) who had at least moderate pruritus at baseline, including 10 of 24 patients (42%) who had blood involvement, 52 months, while median PFS was 29 months for patients with a confirmed or unconfirmed CR. 53 In the study by Piekarz et al, 40 the median TTP was 13.0 months for patients with a CR or PR, 4.6 months for patients with stable disease, or 1.4 months for patients with disease progression.…”
Section: Clinical Efficacymentioning
confidence: 94%
“…However, CMRP also occurred in nonresponders (11/39, 28%)—all with best response of stable disease (SD). Patients were also able to achieve CMRP irrespective of disease compartment involvement; although lymphadenopathy significantly lowered rates of CMRP, erythroderma, blood involvement, and higher blood tumour burden (surrogate for SS) did not [58]. …”
Section: Clinical Studies Of Systemic Anti-lymphoma Agents Includingmentioning
confidence: 99%
“…The definition of complete resolution was more stringent in the study with romidepsin, requiring VAS = 0 for ≥8 vs ≥4 consecutive weeks [56, 71]. Subanalyses of the romidepsin study also showed that patients experienced pruritus reduction irrespective of disease compartment involvement, and in difficult-to-treat populations including patients with cutaneous tumours, folliculotropic MF, and those with prior chemotherapies [58–60]. Importantly, vorinostat trials allowed the use of concomitant anti-pruritic medications, which could impact results, whereas the romidepsin trial did not [56, 71, 72].…”
Section: Summary and Recommendationsmentioning
confidence: 99%